Zimbabwe : 2014 Article IV Consultation-Staff Report; Press Release; and Statement by the Executive Director for Zimbabwe. (IMF Staff Country Reports; Country Report, 2014)
This 2014 Article IV Consultation highlights that economic rebound in Zimbabwe experienced since the end of hyperinflation in 2009 has now ended. After averaging 10 percent over 2009-2012, growth fell to an estimated 3.3 percent in 2013, reflecting tight liquidity conditions, election-year uncertainty, weak demand for key exports, competitiveness pressures, and the impact of adverse weather conditions. Inflation continued its downward trend from 2.9 percent (year over year) at end-2012 to ?0.3 percent in April 2014. The medium-term outlook, under the baseline scenario, is for growth to average some 4 percent, as large mining sector investments reach full capacity.